Selling System Using In Pharmacy Terogong Visual Basic ver. 6.0 - Ema Indrawati Kusumahari; Ir. Syahril (Jurnal Sistem Informasi, 2007)
Computers as a support tool that can solve a wide range problems. Computers became animportant part in the organization of information processing because the power of technologyand the volume of data processed. Computerized data processing transaction is an activitythat is not only done by large organizations. Computerized sales system is very helpful in thetransaction process, and preparing reports. Process transactions and preparing reports to bemore effective, efficient and timely manner.Keywords: System Sales, Transactions